2005
DOI: 10.1037/0894-4105.19.4.428
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory and auditory event-related potentials in Huntington's disease.

Abstract: The influence of Huntington's disease (HD) on the olfactory event-related potential (OERP), an electrophysiological measure of olfactory information processing, has not been reported to date. In the present study, olfactory and auditory event-related potentials (ERPs) were recorded monopolarly from Fz, Cz, and Pz electrode sites in 8 patients with HD and 8 age- and gender-matched control participants. Results demonstrated that individuals with HD were delayed compared with controls on the P3 component of the O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…However, it is now appreciated that htt-induced deficits are more widespread, involving cortex, hippocampus, hypothalamus and olfactory function (Hedreen et al, 1991;Spargo et al, 1993;Murphy et al, 2000;Mitchell et al, 2005;Petersen et al 2005;Wetter et al, 2005). These regions correspond to the specific localization of Bcl11b in the CNS, as described herein, and by others (Leid et al 2004;Arlotta et al 2005;Desplats et al 2006).…”
Section: Discussionsupporting
confidence: 75%
“…However, it is now appreciated that htt-induced deficits are more widespread, involving cortex, hippocampus, hypothalamus and olfactory function (Hedreen et al, 1991;Spargo et al, 1993;Murphy et al, 2000;Mitchell et al, 2005;Petersen et al 2005;Wetter et al, 2005). These regions correspond to the specific localization of Bcl11b in the CNS, as described herein, and by others (Leid et al 2004;Arlotta et al 2005;Desplats et al 2006).…”
Section: Discussionsupporting
confidence: 75%
“…Recently, one group of researchers found deficits in olfactory function in gene carriers who were on average 4.7 years from predicted onset of HD (Wetter et al, 2006). In an olfactory event-related potential (ERP) study, Wetter et al (2005) found that HD patients showed latency delays on the cognitive P3 component of the olfactory ERP. Recently, these researchers used the same ERP task to investigate olfactory functioning in asymptomatic gene carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Olfactory event-related potentials (OERPs) recorded in relation to olfactory stimulation has demonstrated sensitivity to subtle changes in olfactory functioning associated with aging, disease, and ApoE status [36-45]. OERPs require odor stimulation via specially built olfactometers which control the exact timing of stimulus onset while avoiding simultaneous stimulation of other sensory modalities such as stimulation of the trigeminal system [39,46-49].…”
mentioning
confidence: 99%